Brucellosis induced avascular necrosis of the femoral head in a 7 year old child. Issue 3 (March 1992) - Gedalia, A; Howard, C; Einhorn, M
Abstract : The case is reported of a 7 year old Bedouin girl who presented with a three week history of fever and limp. Initial tests for rheumatoid factor, antinuclear antibodies, and brucella were negative. Two weeks after admission Brucella melitensis was cultured from bone marrow and synovial fluid samples. The patient improved after treatment with doxycillin and streptomycin, but radiographs of the right hip showed avascular necrosis of the right femoral head. A mild limp and limitation of motion in the right hip persisted 18 months after admission.